2010
DOI: 10.1002/ejic.201000892
|View full text |Cite
|
Sign up to set email alerts
|

[{2,6‐(Me2NCH2)2C6H3}Sn(μ‐OH)W(CO)5]2: A Transition‐Metal‐Coordinated Organotin(II) Hydroxide

Abstract: Keywords: Tin / Tungsten / X-ray diffraction / Density functional calculations / Organotin hydroxides / Hydrogen bondsThe synthesis of the intramolecularly coordinated pentacarbonyltungsten-organostannylene complexes {2,6-(Me 2 NCH 2 ) 2 C 6 H 3 }Sn(H)W (CO) 5 (2) and [{2,6-(Me 2 NCH 2 ) 2 -C 6 H 3 }Sn(μ-OH)W(CO) 5 ] 2 (3) and the solid-state molecular structure of 3, as determined by single-crystal X-ray diffrac-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…The N1-Sn1 distance of 2.514(2) Å is similar to those found in the corresponding organostannylene {2,6-(Me 2 NCH 2 ) 2 C 6 H 3 }SnCl [2.525(8), 2.602(8) Å] [12] and its tungstenpentacarbonyltin(II) hydroxide [{2,6-(Me 2 NCH 2 ) 2 C 6 H 3 }Sn(μ-OH)W(CO) 5 ] 2 [2.501(7) Å] [10] but longer than the corresponding distance in the aqua complex [{(2,6-Me 2 NCH 2 ) 2 C 6 H 3 }(H 2 O)- SnW(CO) 5 ] + (CB 11 H 12 ) -[2.264(2) Å]. The tin atom is five coordinate and shows a distorted square pyramidal configuration with a square base plane defined by the N1, C1, O1, and O1a atoms with a O1-Sn1-O1a bond angle of 73.68(7)°and a C1-Sn1-N1 bond angle of 73.88(9)°.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…The N1-Sn1 distance of 2.514(2) Å is similar to those found in the corresponding organostannylene {2,6-(Me 2 NCH 2 ) 2 C 6 H 3 }SnCl [2.525(8), 2.602(8) Å] [12] and its tungstenpentacarbonyltin(II) hydroxide [{2,6-(Me 2 NCH 2 ) 2 C 6 H 3 }Sn(μ-OH)W(CO) 5 ] 2 [2.501(7) Å] [10] but longer than the corresponding distance in the aqua complex [{(2,6-Me 2 NCH 2 ) 2 C 6 H 3 }(H 2 O)- SnW(CO) 5 ] + (CB 11 H 12 ) -[2.264(2) Å]. The tin atom is five coordinate and shows a distorted square pyramidal configuration with a square base plane defined by the N1, C1, O1, and O1a atoms with a O1-Sn1-O1a bond angle of 73.68(7)°and a C1-Sn1-N1 bond angle of 73.88(9)°.…”
Section: Resultssupporting
confidence: 74%
“…[6] Driess et al reported silicon(II) hydroxide LSi(OH)Ni(CO) 3 stabilized by a β-diketiminate ligand {L = CH[(CMe)(2,6-iPr 2 C 6 H 3 N)] 2 }. [10] As a part easy hydrolytic protocol. [9] The given examples suggest that the condensation-deprotonation reactions of hydroxides of low-valent group 14 elements are restrained by either sterically demanding substituents or electron-donating ligands.…”
Section: Introductionmentioning
confidence: 99%
“…[53] Notably, the resonances for the complexes 1-4 are more low-frequency shifted than those for complexes 5, 6 and cis- As in the chromium-pentacarbonyl complex [4-tBu-2,6- [51,58] the 1 H NMR spectra of complexes 1-4 each show four doublet resonances for the isopropyloxy methyl protons. As in the related complex [2,6-(Me 2 NCH 2 ) 2 C 6 H 3 (H)SnW(CO) 5 ], [59] the 1 H NMR spectra of complexes 5 and 6 each exhibit two equally intense singlet resonances for the N-methyl protons and AB-type resonances for the methylene protons. No coalescence phenomena were observed, which indicates high configurational stability of the tin atoms.…”
Section: Resultsmentioning
confidence: 77%
“…16 In all the cases, Sn centres carry a lone pair of electrons. However the value of the coupling constant is significantly smaller than that of F ( 1 J Sn-H = 1158 Hz) and [{2,6-(Me 2 NCH 2 ) 2 C 6 H 3 }Sn(H)W(CO) 5 ] (1302 Hz) 12 where the lone pair at the Sn centre coordinates to a Lewis acid. This indicates that the coupling constant is strongly influenced by the nature of surrounding ligands at the Sn centre.…”
mentioning
confidence: 93%
“…11 Moreover, Jurkschat et al outlined the synthesis of [{2,6-(Me 2 NCH 2 ) 2 C 6 H 3 }Sn(H)W(CO) 5 ], a pincer based Sn(II) hydride stabilized in the coordination sphere of W(CO) 5 . 12 This encouraged us to prepare the hitherto elusive terminal Sn(II) hydride.…”
mentioning
confidence: 99%